Pengaruh Kompetensi Profesional Guru Pendidikan Agama Kristen Terhadap Karakter Siswa Kelas IX SMP Negeri 1 Baktiraja Kabupaten Humbang Hasundutan Tahun Pembelajaran 2023/2024 - Rynelsi Banjarnahor; Andar Gunawan Pasaribu; Johari Manik (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
The aim of this research is to find out whether the Professional Competence of Christian Religious Education Teachers has a positive influence on the Character of Class IX Students of SMP Negeri 1 Baktiraja, Humbang Haunjungan Regency, Academic Year 2023/2024. The research method used is a quantitative method with an inferential approach. The population is all 143 Protestant Christian students in Class IX of SMP Negeri 1 Baktiraja, Humbang Hasundutan Regency for the 2023/2024 academic year and a sample of 51 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire with 36 items, namely 18 items for variable the following data: 1) Test the analysis requirements: a) positive relationship test obtained rxy = 0.527 > rtable(=0.05,n=51) = 0.297. b) Testing a significant relationship obtained tcount= 4.340 > ttable(=0.05, dk=n-2=49)= 2.021. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂=